Inner ambient control of the parked vehicle in a hot sunny day by remote access - Azhar, Marsad Latif; Mannan, Abdul; Khan, Md. Raisuddin; Bhuiyan, Moinul; Saleh, Tanveer (2014)
Rise of interior temperature during daytime for a fully locked and parked car is a problem that needs to be addressed. The main reason for this significant rise in interior temperature is the heat that is trapped inside because of the closed glass window. This situation is very uncomfortable for people inside the car especially for toddlers and pets. . Several measures had been proposed and some of them implemented to counter this issue such as leaving the windows partially open for the parked car or installing an external ventilation unit like a blower to regulate the internal temperature. However, none of these solutions are reliable and beneficent and moreover at times leave serious security loopholes apart from other typical drawbacks like power inefficiency and high cost. As of such, there is an immense requirement to come up with a 'smart' and reliable solution for this issue keeping in mind factors like cost, power efficiency, user friendliness and reliability. A smart system has been developed which gives a comprehensive control over the whole car cooling system of the vehicle from a remote area. Moreover, other customizable necessary features like window control, safety and security are also be included. Results shows the proposed system can efficiently bring down the inside temperature of the car to a comfortable range for the passengers.